Grab-, Sarg-, Bau- und Votivinschriften - Janowski, Bernd (2011)
in Verbindung mit Karl Hecker, Andrea Jördens, Jörg Klinger, Heidemarie Koch, Ingo Kottsieper, Matthias Müller, Norbert Nebes, Hans Neumann und Herbert Niehr.